\(\lim\limits_{x\rightarrow+\infty}\left(3x-\sqrt{9x^2+4x}\right)=\lim\limits_{x\rightarrow+\infty}\dfrac{-4x}{3x+\sqrt{9x^2+4x}}=\lim\limits_{x\rightarrow+\infty}\dfrac{-4}{3+\sqrt{9+\dfrac{4}{x}}}=-\dfrac{2}{3}\)
\(\lim\limits_{x\rightarrow+\infty}\left(2x-\sqrt[3]{8x^3+x}\right)=\lim\limits_{x\rightarrow+\infty}\dfrac{-x}{4x^2+2x\sqrt[3]{8x^3+x}+\sqrt[3]{8x^3+x}}=0\)
\(\lim\limits_{x\rightarrow-\infty}\left(2x+\sqrt[3]{8x^3+x}\right)=2x\left(1+\sqrt[3]{1+\dfrac{1}{8x^2}}\right)=-\infty.2=-\infty\)